Responsibility of Local Government Against Sea Pollution, Plastic Waste In Sea Waters, Sorong City - Samosir, Hotlan (Papua Law Journal, 2017)
This study aims to determine the impacts arising from the handling of waste (waste plastic) which is not effective in urban areas. Waste in urban areas that are not handled properly will be wasted into rivers and ends at sea. Increasing the amount of plastic waste in the marine waters of Sorong City can cause disruption to the convenience of sea users, especially for fishermen and tourists who aim to Raja Ampat regency. The wider impact due to increased waste of plastics in the marine waters of Sorong City is able to threaten the marine ecology.Pollution of marine waters of Sorong City is the responsibility of local government that is local government of Sorong City. Efforts to overcome the pollution can be done by streamlining waste management in urban areas by socializing the use of government-provided waste containers provided by local government with color variations to distinguish types of organic waste and non-organic waste and wet garbage. Adjustment needs to be made between the number of residents with the availability of waste disposal facilities and including the janitor so that the waste can be handled up to the landfill (Final Disposal Place).